DYNAMICS OF HEMODYNAMIC INDICATORS DURING INTENSIVE CARE FOR DIABETIC KETOACIDOSIS (American Journal of Interdisciplinary Research and Development, 2024)
Diabetes mellitus (DM) is one of the most common endocrine diseases worldwide. Severe and dangerous complications of diabetes mellitus are diabetic ketoacidosis and hyperglycemic ketoacidotic coma, which require a special approach, both due to the severity of the course and due to high mortality. High mortality in hyperglycemic ketoacidotic coma is associated with insulin deficiency (1,4,6), tissue hypoxia, endogenous intoxication, water-electrolyte imbalance, metabolic disorders, multiple organ dysfunction (2,3,5). Most clinicians identify, first of all, hypovolemia and accompanying systemic hypoperfusion as one of the leading links in the pathogenesis of systemic and organ failure in patients with diabetic ketoacidosis and hyperglycemic ketoacidotic coma (2,6).